THE EFFECT OF SUPERVISOR SUPPORT TO TURNOVER INTENTIONMEDIATING BYCOMPETENCE, PSYCHOLOGICAL EMPOWERMENT AND WORK ENGAGEMENT - Suprihati,; Budiyanto,; Suhermin, (International Journal of Psychosocial Rehabilitation, 2020)
Turnover intention is the intention of employees to stop working from work voluntarily or move from one work place to another according to their own choice.This study aims to analyze the direct effect of supervisor support on turnover intention,and the indirect effect between competence, psychological empowerment and work involvement as a mediating variable on turnover intention.The research method is survey method in which primary data collection is obtained directly from textile industry employees and Central Java textile products.Non-random sampling technique with sampling using accidental sampling with research samples of 270 employees of the textile and textile product industries. Data were analyzed using the Structural Equation Modeling method with AMOS.The results of the data analysis show that competence, psychological empowerment and employee involvement have proven to be capable as mediators of turnover intention.This research has implications as material for evaluation and feedback on efforts to handle and improve employees, especially the handling of turnover intention in the textile industry and textile products.